Application of foam-mat drying to produce field crab powder: Foaming process optimization, drying kinetics, and final product characterization - Nguyen Minh Thuy; Ngo Ngoc Nhut Minh; Nguyen Hoang Kha; Bui Thi Bich Thuy; Tran Ngoc Giau; Hong Van Hao; Vo Quang Minh; Ngo Van Tai (Journal of Agriculture and Food Research, 2025)
This study used foam-mat drying to make powder from field crab meat for the first time. In which, the effect of foaming conditions [egg albumin (EA, 7.96–16.44 %) and xanthan gum (XG, 0.04–0.44 %)] and drying temperature (65–80 °C) on powder quality were examined. With appropriate EA and XG levels of 13.16 % and 0.30 %, foam density and foam expansion were 0.395 g/mL and 279.78 %, respectively. The total energy required and specific energy consumption decreased. In contrast, thermal efficiency and energy efficiency rose with drying temperature, reaching 2.494–4.452 %, and 1.419–1.879 %, respectively. Temperature affects effective moisture diffusion coefficient according to the Arrhenius equation with an activation energy of 39.33 kJ/mol. Fitting experimental data to seven thin-layer drying models and an ANN model. The Aghbashlo model scored best, with the highest correlation coefficient. Nevertheless, the ANN model demonstrated slightly superior accuracy compared to the Aghbashlo model, indicating the potential for industrial system control.